Chimerism in the Realm of Hematopoietic Stem Cell Transplantation for Non-malignant Disorders—A Perspective - Zimmerman, Clare; Shenoy, Shalini (Frontiers in Immunology, 2020)
Abstract: Hematopoietic stem cell transplantation (HCT) is a curative intervention in non-malignant disorders (NMD) that benefit from donor-derived hematopoiesis, immunity, and establishment of vital cells or enzyme systems. Stability or reversal of disease symptoms depends on adequacy and long-term stability of donor cell engraftment in the compartment of interest. Unlike hematologic malignancies where complete replacement with donor derived hematopoiesis is desirable for a cure, NMD manifestations can often be controlled in the presence of mixed chimerism. This allows for exploration of reduced intensity conditioning regimens that can limit organ toxicity, late effects, and increase tolerability especially in young recipients or those with a large burden of disease related morbidity. However, the levels of donor chimerism conducive to disease control vary between NMD, need to focus on the hematopoietic lineage necessary to correct individual disorders, and need to be assessed for stability over time, i.e. a whole lifespan. An enhanced ability to reject grafts due to recipient immune competence, alloimmunization, and autoimmunity add to the complexity of this balance making NMD a highly diverse group of unrelated disorders. The addition of donor factors such as stem cell source and Human-Leukocyte-Antigen match extend the complexity such that ‘one size does not fit all’. In this perspective, we will discuss current knowledge of the role of chimerism and goals, approach to HCT, and emerging methods of boosting engraftment and graft function, and monitoring recommendations. We draw attention to knowledge gaps and areas of necessity for further research and research support.